2019 28th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2019
DOI: 10.1109/ro-man46459.2019.8956332
|View full text |Cite
|
Sign up to set email alerts
|

Learning Active Spine Behaviors for Dynamic and Efficient Locomotion in Quadruped Robots

Abstract: In this work, we provide a simulation framework to perform systematic studies on the effects of spinal joint compliance and actuation on bounding performance of a 16-DOF quadruped spined robot Stoch 2. Fast quadrupedal locomotion with active spine is an extremely hard problem, and involves a complex coordination between the various degrees of freedom. Therefore, past attempts at addressing this problem have not seen much success. Deep-Reinforcement Learning seems to be a promising approach, after its recent su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…This was achieved using Contact-Implicit Optimization methods [36], which have been shown to be a vital tool in studying locomotion [37]- [39], and has been implemented with significantly increased accuracy [34]. This method requires a large number of complementary constraints which can be found in [36] equation (8) to (16). All contacts are modelled as an inelastic collision [36], [40] and can take one of two modes (sticking or slipping).…”
Section: A Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…This was achieved using Contact-Implicit Optimization methods [36], which have been shown to be a vital tool in studying locomotion [37]- [39], and has been implemented with significantly increased accuracy [34]. This method requires a large number of complementary constraints which can be found in [36] equation (8) to (16). All contacts are modelled as an inelastic collision [36], [40] and can take one of two modes (sticking or slipping).…”
Section: A Constraintsmentioning
confidence: 99%
“…These spines often consist of a multitude of actuated rigid links. Despite being common place and crucial in nature, the spine (active [9]- [16] or passive [17]- [21]) is not commonly found in robotics. To date there Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are interested in a smooth trajectory that requires minimal power consumption while maximizing the resulting velocity. e efficiency is the ratio between the input power and the power consumption (i.e., the ratio between the average kinetic energy ∼ v 2 and the input power W, compare with [29]). We also include an additional dimensionless ratio d/T which measures the "straightness" of the path (compare with [37]).…”
Section: E Ga Weight Functionmentioning
confidence: 99%
“…Obviously, using cameras as sensors in the gait optimizing procedure requires real-time techniques for analyzing the video stream (see [27,28]). e back joint (spine) was investigated in [29], where the research studies presented simulations showing that an active back is a key driving factor for the improvement of speed and cost-of-transport in quadrupeds. In [30], Khoramshahi et al presented a simplified (wheeled) locomotion system which is behaviorally and structurally similar to a galloping quadruped and showed that fast locomotion requires a flexible spine.…”
Section: Introductionmentioning
confidence: 99%